2011
DOI: 10.1530/rep-10-0432
|View full text |Cite
|
Sign up to set email alerts
|

Gpr54−/− mice show more pronounced defects in spermatogenesis than Kiss1−/− mice and improved spermatogenesis with age when exposed to dietary phytoestrogens

Abstract: Mice with mutations in the kisspeptin signaling pathway (Kiss1 K/K or Gpr54) have low gonadotrophic hormone levels, small testes, and impaired spermatogenesis. Between 2 and 7 months of age, however, the testes of the mutant mice increase in weight and in Gpr54 K/K mice, the number of seminiferous tubules containing spermatids/spermatozoa increases from 17 to 78%. In contrast, the Kiss1 K/K mice have a less severe defect in spermatogenesis and larger testes than Gpr54 K/K mice at both 2 and 7 months of age. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Around 4-5 months of age, however, condensed sperm heads were found in mutant mice, indicating an increased level of spermiogenesis in older males. We have observed a similar increase previously in Kiss1 KO mice, which we have shown to be a result of exposure to phyto-oestrogens in the mouse chow (16).…”
Section: Resultssupporting
confidence: 88%
“…Around 4-5 months of age, however, condensed sperm heads were found in mutant mice, indicating an increased level of spermiogenesis in older males. We have observed a similar increase previously in Kiss1 KO mice, which we have shown to be a result of exposure to phyto-oestrogens in the mouse chow (16).…”
Section: Resultssupporting
confidence: 88%
“…It might be possible to initiate spermatogenesis in the mutant mice with pulsatile FSH and subcutaneous testosterone delivery. Although we have shown that Kiss1 and Gpr54 mutant mice can initiate a low level of spermatogenesis when given a chow diet containing phytoestrogens (23), the number of sperm that can be isolated from the vas deferens and epididymis is too small for functional studies. It is noteworthy, however, that several male patients with mutations in GPR54 and hypogonadotropic hypogonadism have responded to exogenous hormone treatment and achieved fertility [for review, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mice with mutations in the kisspeptin signaling pathway [e.g., Kiss1(Ϫ/Ϫ) or Gpr54(Ϫ/Ϫ) mice; kisspeptins are a family of peptide hormones that, together with the kisspeptin receptor (previously known as G-protein-coupled receptor 54), play a critical role in the regulation of the hypothalamic-pituitary-testicular axis, such as in the release of 1) gonadotropin-releasing hormone from the hypothalamus and 2) LH and FSH from the pituitary gland (d'Anglemont de Tassigny and Colledge, 2010;Hameed et al, 2011)] were found to have smaller testes and impaired spermatogenesis versus wild-type animals, lacking spermatids in the epithelium as the result of postmeiotic defects. On the other hand, diets supplemented with phytoestrogens (e.g., genistein and daidzein from soy/soybeans) were shown to have a significant improvement in spermatogenesis over a 7-month period with regard to testis weight and the number of elongated spermatids and spermatozoa (Mei et al, 2011). In summary, these findings illustrate that estrogens support somatic cells in the testis and the epididymis, as well as regulate germ cell apoptosis and spermiogenesis, in particular the transition of spermatocytes into round spermatids (Carreau and Hess, 2010;.…”
Section: Tight Junction (Zonula Occludens) and Basal Ectoplasmic Specmentioning
confidence: 99%